Preventive Measures and Management of Catheter-Associated Urinary Tract Infection in Adult Intensive Care Units in Saudi Arabia - Najla A. Obaid (Journal of Epidemiology and Global Health, 2021)
Catheter-associated Urinary Tract Infection (CAUTI) has been studied worldwide as part of device-related healthcare infection. CAUTI is one of the most commonly reported infections in the literature, which occurs during clinical practice in Intensive Care Units (ICUs) and non-ICU departments. Many studies have covered the CAUTI rate in Saudi Arabia mainly in the ICU covering single or multiple hospitals as surveillance for device-related infections in the ICU. Few studies have conducted an interventional approach that examined the implementation of infection control protocols and then compared them to international practice as a standard. This review aims to explore the literature to provide insight into the infection control practices that have been reported in Saudi Arabia during the last two decades on the preventive measures and clinical consequences of CAUTIs. Very few studies have recorded the pattern of resistant microorganisms that burdens clinical practice in ICUs concerning CAUTIs. Only one study compared the type of catheter materials and discussed the effect of these materials on reducing CAUTIs. It is essential to cover catheter utilization and to understand how a sufficient infection control protocol with educational programs for healthcare personnel can transform practice, for the better, regarding CAUTI rates in Saudi hospitals. There is a demand for more interventional and epidemiological studies on the causes and factors affecting the rate of CAUTI in the area. Studies may help reduce the CAUTI incidence rate, which consequently reduces the costs and morbidity associated with this type of infection and other healthcare-related infections.